Effects of Nitrogen Load on the Function and Diversity of Methanotrophs in the Littoral Wetland of a Boreal Lake - Siljanen, Henri M.; Saari, Anne; Bodrossy, Levente; Martikainen, Pertti J. (Frontiers in Microbiology, 2012)
Methane is the second most abundant greenhouse gas in the atmosphere. A major part of the total methane emissions from lake ecosystems are emitted from littoral wetlands. Methane emissions are significantly reduced by methanotrophs as they use methane as the sole energy and carbon source. Function of methanotrophs can be either activated or suppressed by nitrogen. However, the effects of nitrogen on methanotrophs in littoral wetlands are unknown. Here we report how nitrogen loading in situ affected the function and diversity of methanotrophs in a littoral wetland. Methanotrophic community composition and functional diversity were analyzed with particulate methane monooxygenase (pmoA) gene targeted microarray. Nitrogen load had no effects on methane oxidation potential and methane fluxes. Nitrogen load activated pmoA gene transcription of type I (Methylobacter, Methylomonas and LW21-freshwater phylotypes) methanotrophs, but decreased the relative abundance of type II (Methylocystis, Methylosinus trichosporium and Methylosinus phylotypes) methanotrophs. Hence, the overall activity of a methanotroph community in littoral wetlands is unlikely to be affected by nitrogen leached from the catchment area.